Effects of magnesium sulphate and nitric oxide in pulmonary hypertension induced by hypoxia in newborn piglets. Issue 3 (November 1994) - Ryan, C A; Finer, N N; Barrington, K J
Abstract : AIM--To examine the haemodynamic effects of intravenous magnesium sulphate on an animal model of neonatal pulmonary hypertension induced by hypoxia. METHODS--The cardiac index (Q), pulmonary arterial pressure (PAP), systemic arterial pressure (SAP), and pulmonary (PVRI) and systemic (SVRI) vascular resistance indices were measured in nine newborn piglets (including three controls). Pulmonary hypertension was induced by lowering the FIO2 to 0.12-0.14, after which there was a significant increase in PAP and PVRI (37% and 142%, respectively; p < 0.01) and a significant fall in SAP and Q (30% and 33%, respectively; p < 0.01). RESULTS--Magnesium sulphate was infused intravenously as four doses of 25 mg/kg, 15 minutes apart, which resulted in a significant mean (SD) increase in serum magnesium (0.83 (0.07) mmol/l to 1.82 (0.19) mmol/l; p < 0.01). After the initial dose SAP, SVRI, PAP and PVRI decreased, but not significantly. Each subsequent dose of (50, 75, 100 mg/kg) was accompanied by further significant reductions in these variables from control baseline (p < 0.05). The PVRI:SVRI ratio remained unchanged throughout. Inhaled nitric oxide (NO) 40 ppm was administered after the last dose of magnesium sulphate. The PVRI:SVRI significantly decreased (p < 0.05), indicating that reversible pulmonary hypertension remained after a maximum dose of magnesium sulphate. CONCLUSIONS--Unlike NO, magnesium sulphate is not a selective pulmonary vasodilator and may lead to deleterious effects on systemic pressures in critically ill newborns.